Comparative analysis of PCM configurations for energy-efficient air conditioning systems: A case study in Riyadh, Saudi Arabia - Abdulaziz Alasiri; Mohamed Nasser (Case Studies in Thermal Engineering)
This study examines the integration of Phase Change Materials (PCM) with air conditioning (AC) systems to address the challenge of high energy consumption in buildings, particularly in hot climates such as Riyadh, Saudi Arabia. The PCM unit is employed before the AC condenser as an air cooler. Three scenarios are conducted: a base AC without PCM and an AC with flat and corrugated PCM plates. Through numerical simulation and experimental validation, the study demonstrates optimistic improvements in system performance. The integration of PCM resulted in annual energy savings of 7.6 % and 8.6 % for corrugated and flat PCM structures, respectively. The cooling effect lasted approximately 7 h during summer months, with maximum air temperature differentials across the PCM unit of around 3 °C observed in July and August for the corrugated PCM structure. The study employed comprehensive thermodynamic analysis and computational fluid dynamics to evaluate system performance across different summer months conditions. Results show that PCM integration effectively reduces peak cooling loads and improves overall system efficiency. The findings demonstrate that both PCM configurations offer viable solutions for enhancing AC system performance in hot climates, with the flat PCM showing slightly superior energy savings despite the corrugated design's better initial cooling performance.